Perceived Inflation as a Determinant of the Savings and Spending Structure of Consumers - Andreas Krämer; Daniel F. Heuermann; Thomas Burgartz (Wirtschaftsdienst)
Abstract In Europe and the U. S., official inflation rates reached a level of around 7 %–8 % in mid-2022. Based on survey data for Germany, we show that there is a rising gap between the objective (administrative) inflation rate and the (subjective) inflation rate as perceived by consumers, which is around 13 %. Low-income households are particularly affected by rising prices. Across all income groups, consumers react to rising prices by means of purchasing and consumption restraints, which runs counter to an assumed preference for the present as postulated by classical macroeconomics.